The use of natural (Pinus pinaster) resin in the production of printing ink and the printability effect - AYDEMİR, CEM; ARMAN KANDIRMAZ, EMİNE; YENİDOĞAN, SEMİHA (WILEY, 2020)
Alkyd resins are generally used in the production of printing inks. All industries look for alternative raw materials in the production of ink with the growing inclination toward using natural products. Resins forming the vehicle of the ink to be obtained from natural resources will provide benefits for the environment, nature, and living creatures. The aim of the study was to promote the use of natural resin in the ink system. NaturalPinus pinasterresin was added into vegetable and mineral oil-based solvents in pure form with alkyd resin in different amounts and ink varnishes of different combinations were prepared. Then, printing inks were produced from these varnishes in pure and hybrid form. Following the assessment of the rheological properties of the inks prepared, printing tests were conducted to assess the printing quality parameters. Ideal mixing ratios of the natural resins in the ink were determined for printability. The environmental importance and advantages of the use of natural resins were discussed. Recommendations were given in line with the results to encourage widespread use of natural resins in near future.
Keywords: bio-compatible; natural resin; Pinus pinaster; printability; printing ink; QUALITY; PAPER